Molecular phylogeny and morphological characterization revealed Lepiota brunneoaurantia, a new species in L. sect. Stenosporae from Margalla Hills, Pakistan - Azeem, Memoona; Kiran, Munazza; Jabeen, Sana (Phytotaxa, 2024)
Lepiota brunneoaurantia sp. nov. was collected from the Margalla Hills, Pakistan. This species was characterized by an orangish brown pileus with a dark brown umbo, presence of orangish upturned, crowded squamules, close off-white lamellae having lameullae of variable lengths, small (5.6 × 2.5 µm), oblong to ellipsoid basidiospores and clavate cheilocystidia. Comparative study based on morphology and molecular phylogeny revealed that it is distinct from already known taxa in the genus and represent a new species.